The Effect of Leadership Style, Work Environment, and Work Motivation on Employee Performance PT. Sentral Bra Makmur in Bogor (Lembaga Pengembangan Kinerja Dosen, 2025)
A company's human resource potential is basically one of the important capital and plays the most important role in achieving company goals. In producing good performance, leadership style, work environment and work motivation are a big influence for PT. Sentral Bra Makmur. The purpose of this study was to determine the effect of leadership style, work environment and motivation on the performance of employees of PT Sentral Bra Makmur in Bogor. This research is in the form of quantitative and qualitative research with data sources from primary data. The technique of sampling used accendintal sampling method with a sample of 100 respondents. The data analysis technique used is multiple regression analysis, t test, F test and coefficient of determination (R2) test. The results showed that leadership style had a significant effect on the performance of employees of PT Sentral Bra Makmur, the work environment had an insignificant effect on the performance of employees of PT Sentral Bra Makmur and work motivation had an insignificant effect on the performance of employees of PT Sentral Bra Makmur.